Storytelling Dalam Al-Quran Sebagai Metode Bimbingan Konseling Islam - Chandra; Agustina, Naimah (AL-IBROH: Jurnal Ilmu Pendidikan dan Keguruan, 2024)
Storytelling during the learning process in Madrasah Ibtidaiyah has become an integral part of Islamic Education. It is considered an effective tool for passing down values from generation to generation, as well as shaping the identity and personality of students. This study aims to investigate the role and impact of storytelling in promoting the formation of students' identity and personality in Islamic Elementary Schools. Through qualitative methods, this research explores storytelling. It employs a library research approach by analyzing literature and related texts. The findings of this research indicate that several real-life stories influence students' understanding of values in Madrasah Ibtidaiyah, including stories about the prophets, tales of children with good character, stories emphasizing the importance of politeness, justice, and honesty. It is noted that storytelling has a significant impact on shaping religious identity, students' self-identity, and their values, thus strengthening the relationship between teachers and students within the Madrasah Ibtidaiyah environment.